Legal Study of Posita and Petitum Conflicts in Lawsuits Over Land Objects: Kajian Hukum Terhadap Pertentangan Posita dan Petitum Dalam Gugatan Atas Objek Tanah - Arifina Alanis, Arselin; Ravani, Shakila; Nailul Muna, Intan; Alice Reyhanif, Alvieta; Suwandoko, Suwandoko (Mendapo: Journal of Administrative Law, 2025)
This study analyzes the legal implications arising from inconsistencies between posita and petitum in civil litigation, with reference to District Court Decision No. 47/Pdt.G/2024/PN Mkd concerning a land ownership dispute. The procedural defect emerged when the plaintiff’s factual assertions indicated a breach of contract (wanprestasi), whereas the relief sought in the petitum was premised upon an unlawful act (tort/PMH). Such inconsistency results in substantive and procedural ambiguity, rendering the claim potentially defective as an obscuur libel. The research aims to examine the legal reasoning adopted by the panel of judges and to assess the juridical consequences of the contradictory pleadings. Employing an empirical juridical method, the study incorporates courtroom observation, interviews with the presiding judge, and a case approach supported by statutory provisions, court decisions, and doctrinal legal literature. The findings demonstrate that the court concluded the claim failed to establish a coherent nexus between the asserted legal grounds and the relief requested, thereby warranting a ruling of inadmissibility (Niet Ontvankelijk Verklaard). This underscores the fundamental procedural rule requiring consistency and clarity between the elements of a pleading to uphold legal certainty and procedural order in civil proceedings. Accordingly, litigants must articulate legal arguments and requested remedies in a synchronized and legally grounded manner to avoid procedural dismissal and ensure substantive judicial examination.